DESCARTES , INDIFFERENT DECEIVER, AND RADICAL INTERPRETATION - Rogonyan, Garris (Problemos, 2016)
The aim of this paper is to show how and why the method of radical interpretation can solve the problems that are formulated in a variety of sceptical scenarios. First of all, the method of radical interpretation deprives Cartesian sceptical scenario – both in its traditional and more recent versions – of the status of philosophical problem appealing to the difference between intended and unintended lies. The paper also formulates an argument in favour of expanded version of naturalized epistemology due to the introduction of social factors. In particular, there are always at least two necessary limitations imposed by the communication of our hypothesis about knowledge and delusion. In addition, the article explains the need of a moderate externalism (both perceptual and social) for the variants of Descartes and Hume’s sceptical scenario.
Keywords: epistemological scepticism; radical interpretation; communication; externalism